Myrmecophily - Lowdon, Andrew Gilchrist Ross (The University of Edinburgh, 1933)
Any theory of myrmecophytism must still be a matter of personal opinion, for although the available evidence has been considerably increased by the recent work of Bequaert, Bailey, Melin and others, it is not yet possible to draw any definite and final conclusions. The following statement, therefore, expresses only the present status of the problem of myrmecophytism.

Certain plants show structural peculiarities such as fistulose stems, hollow nodal or internodal hypertrophies, hollow petioles, saccate leaves, enlarged stinulär organs, etc., and sometimes in addition extrafloral nectaries or food-bodies. The origin and function of these structures is still obscure. In a great many cases these hollow stems etc. are utilized by ants as domatia, and the nectaries and food -bodies used as sources of food. The ants usually have to construct entrances to their new homes. Some of these ants are obligatory and others facultative inhabitants of the myrmecophytic plants. In many cases the domatia contain, in addition to the ants, growths of fungi and numerous nematodes and coccids. The coccids usually feed upon certain traumatic tissues induced by the ants; the ants solicit and feed upon the exudates of the coccids, and in some cases feed also upon the coccids themselves, the nematodes and the traumatic tissues. They obtain carbohydrate from the extrafloral nectaries, and fat and protein from the food -bodies when these are present. The ants thus obtain both food and shelter from the plants. It appears to be unusual, however, for the ants to have no extraneous sources of food.

The ants, in a few cases, provide to the plant a certain amount of protection against phytophagous enemies, but in no case is this protection such as could be supposed to compensate for the loss suffered by the plant, or to justify a hypothesis of a symbiotic relationship. The ants appear, therefore, to be parasites upon the plants, availing themselves of the structural peculiarities in a singularly efficient manner.
Myrmecophily: written for the Anderson-Henry Prize in Botany, 1933